Symbolic Action: Representation of Bugis-Makassar Ethnicity through Palomba Lopi-lopi in West Nusa Tenggara - Sarah, Fidlia Mae Mae; Musadad, Akhmad Arif; Pelu, Musa (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study examines Palomba Lopi-lopi, a traditional mini sailboat game from Labuhan Kertasari, NTB, as a symbolic representation of migration and Bugis-Makassar ethnic identity. Using Symbolic Action Theory and historical qualitative methods, the study finds that this game is not merely entertainment, but is rich in profound philosophical values. Lopi-lopi symbolizes independence and harmony with nature, while the sea breeze represents human-environment collaboration. The straight course and wide finish line reflect the importance of strategy and precision in achieving goals, while the use of natural materials (kapok wood) underscores local wisdom. The Palomba Lopi-lopi also serves as a historical marker of the Bugis-Makassar ethnic group's migration to Sumbawa following the Bongaya Treaty (1667) and as a form of resistance against Dutch colonialism. Through this game, the community of Labuhan Kertasari preserves their ancestral cultural identity amid the challenges of globalization. Research findings emphasize the importance of preserving this maritime cultural heritage of the Nusantara through documentation and integration into education.